Maintenance vs. Change of Negative Therapy Expectation: An Experimental Investigation Using Video Samples - Braun-Koch, Kristina; Rief, Winfried (Frontiers in Psychiatry, 2022)
Introduction Therapy expectations contribute substantially to the outcome of psychotherapy. In contrast, psychotherapy expectations are rarely addressed and systematically optimised in studies on psychotherapy. Materials and Methods A total of 142 mostly healthy participants with critical attitudes towards psychotherapy were randomised into two groups: (1) a control group that watched a video with patients who gave information about their symptoms or (2) an experimental group that watched an expectation-optimised video with the same patients giving additional information about their mostly positive therapy outcomes. The primary outcome was the Milwaukee Psychotherapy Expectation Questionnaire (MPEQ), which was filled in before and after watching the video. Results Both groups showed a significant improvement of their process expectations and attitudes towards psychotherapy after watching the video. Participants in the experimental group changed their therapy outcome expectation while there was no change in the control group [F(1,140) = 9.72, p = 0.002, η2 = 0.065]. Conclusion A video intervention with patients presenting their positive therapy experiences improves therapy expectations in persons with critical attitudes. Expectation-optimised videos could be used for prevention programmes and when starting therapy. Trial Registration Trial was registered at clinicaltrials.gov (NCT03594903) on November 2018.